Trilhas e rastros da educação primária: história do Grupo Escolar Coronel José Teófilo Carneiro, Uberlândia-MG, 1940-1970 - Ramos, Geovanna de Lourdes Alves (2014)
The theme of this thesis talks about the history of the school group Coronel José Teófilo Carneiro during the period of 1946, the year of your inauguration until 1971 when, by the law 5.692, the groups were extinct and primary education was being taught in public and private schools, as were also modified to suit your teaching first grade curriculum institutions the question that underpins the search consists in understanding the finalities and representation attributed to Group School Coronel José Teófilo Carneiro and that served as justification for it opening and stay as institution of primary education of Uberlândia. In this direction, the goals that have guided the search were: a) learn the characteristics of the school environments through the analysis of the school building infrastructure their architectural aspect as well as its geographical location; b) analyze the profile of the subjects who worked in the institution, teachers and students, in order to discuss the formation of the first and the age, sex and social origins of the seconds; c) learn the representations built on teacher and student; d) discuss the educational legislation produced in the period and peer into how this legislation was appropriate for teachers in the organization of school work; e) discuss teaching practices and tactics employed by teachers in daily classroom; f) understand the existing relations of sociability among students and developed during the civic celebrations, as in other festive events promoted by the institution. We used the following sources: school documents (minutes, logbooks, enrollment, student activities), local media (newspapers), pedagogical press (Journal of Teaching, Educating The Magazine) education legislation (decrees, teaching code IM), programs of the State Department of Education of Minas Gerais and photographs. The files were consulted: Public Archives of Uberlândia (ARPU), Miner Public Archive (APM), the Archives researched School and Personal Files. We conclude that the School Group Colonel José Teófilo Carneiro provides primary education to the working class and its construction in the Workers\' Village - a local stigmatized in the period - sought , through educational practices , instruct students in the principles and patterns of the Republic .